2018
DOI: 10.1002/hed.25557
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of relapsed human papillomavirus‐related oropharyngeal squamous cell carcinoma treated with curative intent

Abstract: Background With most centers reporting excellent disease control following transoral surgery for human papillomavirus (HPV)‐related oropharyngeal cancer, data are still lacking regarding management and outcomes in patients who relapse. We describe the treatment outcomes after curative intent therapy for locoregional and distant relapse following transoral surgery for HPV‐related oropharyngeal squamous cell carcinoma (OPSCC). Methods A single institution retrospective study in which patients were identified wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Some Authors reported that the presence of an LRr may be a predictor of developing DM, despite excellent loco-regional control of the recurrence. 33 This study has some limitations. Firstly, the retrospective design makes the results prone to recall bias or misclassification bias.…”
Section: Discussionmentioning
confidence: 91%
“…Some Authors reported that the presence of an LRr may be a predictor of developing DM, despite excellent loco-regional control of the recurrence. 33 This study has some limitations. Firstly, the retrospective design makes the results prone to recall bias or misclassification bias.…”
Section: Discussionmentioning
confidence: 91%
“…The recurrence of OPSCC after TORS was analyzed by subsite in 13 studies [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. There was no statistically significant difference in the odds of total recurrence between tonsillar and BOT OPSCC (1.1 [95%CI 0.8–1.5], p = 0.480) ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…LRP represents treatment failure of definite therapy in curative intent, with few remaining satisfactory options: Salvage surgery and irradiation are commonly associated with increased morbidity and impaired functionality; and while new immune checkpoint inhibitors alone or in addition to conventional systemic treatment improved outcome in patients not amenable to localized therapy, long-term control of relapsed HNSCC often remains fairly poor [39] , [40] , [41] . Locoregional relapse is also strongly tied to poor overall survival in HPV-associated OPSCC [ 8 , 10 ], substantiating the importance of this endpoint for therapeutic decision making in OPSCC.…”
Section: Discussionmentioning
confidence: 99%